421 Cadmium intake as a prognostic factor in endometrial cancer: a swedish cohort-based study. (18th September 2019) - Razumova, Z; Östensson, E; Mints, M
Abstract : Objectives: Metalloendocrinology is a newly-termed interdisciplinary field. It was established due to the high importance of connections between inorganic chemicals and hormonal mechanisms in the human body. The estrogenic effect of cadmium in hormone-related tumours, such as endometrial cancer (EC), is an excellent example of it. Therefore, the present study aimed to investigate the role of dietary cadmium intake in the prognosis of EC. Methods: The study is based on a large cohort of Swedish women (n=416) who had a hysterectomy and bilateral salpingo-oophorectomy due to EC at the Karolinska University Hospital Solna between 2007 and 2012. Patients from the cohort answered particular questions concerning their lifestyle and dietary habits using the food frequency questionnaire (FFQ). The dietary cadmium intake from each food item was estimated using the FFQ, comprehensive database on the cadmium content, and average daily consumption of different food items. The calculated metal intake was grouped into tertials. The tertials were analysed in connection with different tumour characteristics and clinical outcomes of EC. Results: The average estimated dietary cadmium intake per day in the cohort was 13.9 μg/day. Interestingly, the cadmium input from cereal products and vegetables, mainly considered healthy, in the cohort was dominant. Among 3366.6 person-years of follow-up a total, of 54 incident cases of recurrent EC were identified. A statistically significant association between dietary cadmium exposure and progression-free survival was observed in the cohort (IRR=1.421, 95 CI=.775–2.605, p=0.041). Conclusions: Our results support the hypothesis that dietary cadmium intake may have a prognostic role in patients with EC.